Liver damage promotes pro‐inflammatory T‐cell responses against apolipoprotein B‐100. (13th January 2022) - Plochg, Bastian F. J.; Englert, Hanna; Rangaswamy, Chandini; Konrath, Sandra; Malle, Mandy; Lampalzer, Sibylle; Beisel, Claudia; Wollin, Salma; Frye, Maike; Aberle, Jens; Kluwe, Johannes; Renné, Thomas; et al.
Abstract: Objectives: Liver‐derived apolipoprotein B‐100 (ApoB100) is an autoantigen that is recognized by atherogenic CD4 + T cells in cardiovascular disease (CVD). CVD is a major mortality risk for patients with chronic inflammatory liver diseases. However, the impact of liver damage for ApoB100‐specific T‐cell responses is unknown. Methods: We identified ApoB100‐specific T cells in blood from healthy controls, nonalcoholic fatty liver disease (NAFLD) patients, and CVD patients by activation‐induced marker expression and analyzed their differentiation pattern in correlation to the lipid profile and liver damage parameters in a cross‐sectional study. To assess the induction of extrahepatic ApoB100‐specific T cells upon transient liver damage in vivo, we performed hydrodynamic tail vein injections with diphtheria toxin A (DTA)‐encoding plasmid in human ApoB100‐transgenic mice. Results: Utilizing immunodominant ApoB100‐derived peptides, we found increased ApoB100‐specific T‐cell populations in NAFLD and CVD patients compared to healthy controls. In a peptide‐specific manner, ApoB100 reactivity in healthy controls was accompanied by expression of the regulatory T (Treg)‐cell transcription factor FOXP3. In contrast, FOXP3 expression decreased, whereas expression of pro‐inflammatory cytokine interleukin (IL)‐17A increased in ApoB100‐specific T cells from NAFLD and CVD patients. Dyslipidemia and liver damage parameters in blood correlated with reduced FOXP3 expression and elevated IL‐17A production in ApoB100‐specific T‐cell populations, respectively. Moreover, DTA‐mediated transient liver damage in human ApoB100‐transgenic mice accumulated IL‐17a‐expressing ApoB100‐specific T cells in the periphery. Conclusion: Our results show that liver damage promotes pro‐inflammatory ApoB100‐specific T‐cell populations, thereby providing a cellular mechanism for the increased CVD risk in liver disease patients. Abstract :